2010 Ninth International Conference on Machine Learning and Applications 2010
DOI: 10.1109/icmla.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species Classification Using a 3D LIDAR Sensor and Machine Learning

Abstract: Abstract-In the domain of agricultural robotics, one major application is crop scouting, e.g., for the task of weed control. For this task a key enabler is a robust detection and classification of the plant and species. Automatically distinguishing between plant species is a challenging task, because some species look very similar. It is also difficult to translate the symbolic high level description of the appearances and the differences between the plants used by humans, into a formal, computer understandabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Stereo vision is the method of reconstructing three‐dimensional (3D) surfaces from images taken from multiple 2D sensors by synthesizing objects from different views, and has been applied to plant recognition . The main challenge in using stereo vision for field‐based agricultural systems is the correspondence searching problems caused by the lack of leaf texture, the complexity of the canopy structure, occlusion, and variation in sunlight conditions …”
Section: Introductionmentioning
confidence: 99%
“…Stereo vision is the method of reconstructing three‐dimensional (3D) surfaces from images taken from multiple 2D sensors by synthesizing objects from different views, and has been applied to plant recognition . The main challenge in using stereo vision for field‐based agricultural systems is the correspondence searching problems caused by the lack of leaf texture, the complexity of the canopy structure, occlusion, and variation in sunlight conditions …”
Section: Introductionmentioning
confidence: 99%
“…Studies of crop or weed plant detection using range data have been reported. Three types of state-of-the-art range sensors were commonly used in agricultural applications, including stereo-vision, LiDAR, and TOF sensors (Weiss, Biber, Laible, Bohlmann, & Zell, 2010). Stereo-vision extracts the distance between the sensor and objects in the field-of-view using images acquired with multiple cameras and exploits advantages of high image resolution, available color information, and detailed textural information (Kise, Zhang, & Rovira Más, 2005), while challenged by sensitivity to illumination and high computational requirements (Tippetts, Lee, Lillywhite, & Archibald, 2016).…”
mentioning
confidence: 99%
“…The RANSAC is a commonly used algorithm for evaluating plane parameters in noisy point cloud data [12], [13]. But also for row or line estimation in image analysis [1], and 2D-LIDAR data [14], [15].…”
Section: Ransac Algorithmmentioning
confidence: 99%